RISK AND TURNOVER FROM INVESTING IN EQUITY MUTUAL FUND PERFORMANCE - Abshor Marantika; Nurfiana Nurfiana (Proceeding International Conference on Information Technology and Business, 2016)
Measurement of equity funds committed so far, that was done several previous studies have only done manually, so the process is more vulnerable to errors, the result is a slower, less accurate, less rapidly. The findings of this study with previous differentiate is in the measurement of equity funds used all approaches methods Sharpe, Mayer, Treynor and Jensens models, and information sharpe ratio, also financial information system applications as media performance measurement system in mutual fund shares. Knowing how to interpret this information correctly will make it easier for investor to make responsible and informed investment recommendations to their investors.Based on the calculation results in mutual and stock, mix and fixed income using the Sharpe model of it, it can be concluded that the fund Batavia Shares Fund Optimal who had the best performance, this is caused because reksdana Batavia equity fund Optimal has a return value of the highest in comparison with other funds. Based on the calculation results in mutual and stock, mix and fixed income using methods Sharpe, Mayer, Treynor and Jensens models then, it can be concluded that the fund Shares Fund Optimal who had the best performance, this is caused because reksdana Batavia equity fund Optimal has a return value of the highest in comparison with other funds Key Words : Risk, Turnoverr, Mutual Fund Performance